(untitled) (UUM Journal of Legal Studies, 2020)
The formulation of the National Policy on Industrial Revolution 4.0 (IR4.0) and Internet of things signals the Malaysian government readiness to come up with the necessary policy framework for the digitalised era. It has been said that universities’ curriculum structure and instructional design must also be revisited to ready the graduate to face the onslaught of technological revolution. Through content analysis of relevant literature, this paper analyses the myriad ways in which legal education has been impacted by IR4.0 both in terms of the ‘body of knowledge’ as well as the ‘skill sets’ required for law students to survive in the era of automatous systems. The paper is structured to first explain the concept of IR4.0 and how some national countries leverage the digital technology to improve their economy or facilitate social transformation. The paper proceeds with a discussion of how autonomous system, artificial intelligence and data analytics can enhance the instructional design of teaching and researching law. In terms of the body of knowledge, most of the legal principles drawn for the brick and mortar environment are no longer relevant in the IR4.0 era. The paper reveals that the traditional method that focuses on the training of law graduates to think like a lawyer by understanding the reasoning in the judgement of cases or the preparation of conveyancing and court documents are no longer relevant in the IR4.0 era as these activities could easily be undertaken by bots. Instead, law students should be imparted with a multiplicity of human skills that could not be performed by autonomous systems such as those involving conscience, high level thinking, and emotion such as mediation, negotiation, counselling, court prosecution, advocacy, witness examination, plea mitigation as well as social skills, resource management skills, technical skills and most importantly system skills.